1995
DOI: 10.1007/bf02063953
|View full text |Cite|
|
Sign up to set email alerts
|

Long-term prospective study ofHelicobacter pylori in nonulcer dyspepsia

Abstract: Helicobacter pylori is present in up to 87% of patients with nonulcer dyspepsia. This study assessed the effect of eradicating Helicobacter pylori infection on the symptoms of nonulcer dyspepsia at four weeks and one year after treatment. Dyspepsia was assessed on the frequency and severity of six symptoms [epigastric pain (night and day), nausea and vomiting, upper abdominal discomfort, and regurgitation] where each symptom was scored from 0 to 4. Helicobacter pylori status was assessed before treatment and f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
62
0
2

Year Published

1996
1996
2002
2002

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 131 publications
(66 citation statements)
references
References 25 publications
2
62
0
2
Order By: Relevance
“…The need for longterm follow-up in NUD trials was highlighted by a study of 84 patients receiving eradication therapy followed-up for 1 year. 206 H. pylori was eradicated in 49% of patients and, initially, there was no difference in dyspepsia symptoms between infected and uninfected cases. There was, however, a significant improvement in dyspepsia scores in H. pylori-eradicated patients compared with those remaining infected at 1 year.…”
Section: Introductionmentioning
confidence: 91%
See 1 more Smart Citation
“…The need for longterm follow-up in NUD trials was highlighted by a study of 84 patients receiving eradication therapy followed-up for 1 year. 206 H. pylori was eradicated in 49% of patients and, initially, there was no difference in dyspepsia symptoms between infected and uninfected cases. There was, however, a significant improvement in dyspepsia scores in H. pylori-eradicated patients compared with those remaining infected at 1 year.…”
Section: Introductionmentioning
confidence: 91%
“…Nevertheless, it emphasises the need for longterm follow-up in trials assessing H. pylori eradication in NUD. 206 Recently, a number of large, well-designed, placebo-controlled trials evaluating H. pylori therapy in NUD have been conducted. 207,208 These have avoided the criticisms of earlier studies but have still given conflicting results.…”
Section: Introductionmentioning
confidence: 99%
“…Early reports on the coexistence of gastritis in patients with reflux oesophagitis or reflux symptoms may suggest gastritis, especially of the cardias, as one such factor [7][8][9]. On the other hand, the demonstration of a close relationship between Helicobacter pylori gastritis and peptic ulcer [10][11][12][13] suggested a similar correlation between H. pylori gastritis and non-ulcer dyspepsia, especially with ulcer-like symptoms [9,[14][15][16], despite controversial findings [17,18] and considerable criticism [19].…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have produced contradictory results. McCarthy et al (16) studied 83 patients with functional dyspepsia and HP and reported significantly impaired symptoms in untreated patients or those with reinfection.…”
mentioning
confidence: 99%